Anthropogenic contamination sources drive differences in antimicrobial-resistant Escherichia coli in three urban lakes - Wight, Jordan; Byrne, Alexander S.; Tahlan, Kapil; Lang, Andrew S. (Applied and environmental microbiology, 2024)
A One Health perspective is crucial to understand the extent of antimicrobial resistance (AMR) globally, and investigation of AMR in the environment has been increasing in recent years. However, most studies have focused on waterways that are directly polluted by sewage, industrial manufacturing, or agricultural activities. Therefore, there remains a lack of knowledge about more natural, less overtly impacted environments. Through phenotypic and genotypic investigation of AMR in Escherichia coli , this study adds to our understanding of the extent and patterns of resistance in these types of environments, including over a time series, and showed that complex biotic and abiotic factors contribute to the patterns observed. Our study further emphasizes the importance of incorporating the surveillance of microbes in freshwater environments in order to better comprehend potential risks for both human and animal health and how the environment may serve as a sentinel for potential future clinical infections.